P-182 Improving education on low residue diets in palliative care. (19th November 2022) - Broadbent, Anna; Clode, Lynsey; Stark-Toller, Claire
Abstract : Background and aims: Partial or complete bowel obstruction is a common complication of advanced cancers within the abdominal cavity (Tuca, Guell, Martinez-Losada, et al., 2012. Cancer Manag Res. 159). Following a low residue diet may be part of the treatment of bowel obstruction and may reduce nausea, vomiting and abdominal pain (Vanhauwaert, Matthys, Verdonck et al., 2015. Adv Nutr.6: 820). Methods: A quality improvement project was conducted to provide a new leaflet explaining low residue diets for hospice patients. Surveys were conducted assessing understanding of low residue diets before and after the introduction of a dietician-approved leaflet. Results: Surveys were completed by five patients and twelve staff members (doctors, nurses and healthcare assistants) before and after the introduction of the dietician-approved leaflet. Following leaflet introduction, self-rated confidence in identifying low residue foods increased, on average, by 84% in staff and 147% in patients. For questions in which survey responders identified which food groups were safe to eat, responses improved or remained at the maximum score for 58% of staff and 60% of patients. Qualitative feedback reported that the leaflet was ' clear and practical ' and identified areas for improvement, including adding recipe ideas or more colour and pictures. Conclusion: The introduction of a low residue diet information leaflet has demonstrated efficacy in education, with a meaningful increase in patient self-reported confidence at identifying low residue foods. Areas for future development include improving the leaflet visually, adding supporting posters in the hospice, and highlighting on menus which meals are low residue.